2021
DOI: 10.1021/acssuschemeng.1c05456
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Tolerant Pt/CeO2 Catalyst with Enhanced Oxygen Storage Capacity by Controlling the Pt Content for the Waste-to-Hydrogen Processes

Abstract: In the Pt/CeO2 catalyst, we found that the loading amount of Pt affects not only the dispersion of Pt but also the interaction between Pt and CeO2, specifically to the oxygen storage capacity. The interface between Pt and CeO2 has some special properties due to oxygen reverse spillover, which affects the oxygen storage capacity of the catalyst. The loading amount of Pt in the Pt/CeO2 catalyst was varied from 0.1 to 10.0 wt %, and the physicochemical properties were compared. The prepared samples were tested to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The quantity of this property by the Ce 3+ /Ce 4+ redox couple, which can be reversibly converted in the fluorite structure of CeO 2 , is called the oxygen storage capacity (OSC). In our previous studies, we confirmed that the oxygen reverse spillover caused by the interaction between the active metal Pt and the CeO 2 support and the excellent OSC of the CeO 2 support positively influenced the catalyst activity and sulfur tolerance in the WGS reaction [11][12][13][14][15]. It is noteworthy that various preparation parameters, such as reaction temperature, reaction time, precursor concentration, solvent, and pH, can be used to modify the characteristics of nanomaterials, including OSC, active metal dispersion, and redox properties.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…The quantity of this property by the Ce 3+ /Ce 4+ redox couple, which can be reversibly converted in the fluorite structure of CeO 2 , is called the oxygen storage capacity (OSC). In our previous studies, we confirmed that the oxygen reverse spillover caused by the interaction between the active metal Pt and the CeO 2 support and the excellent OSC of the CeO 2 support positively influenced the catalyst activity and sulfur tolerance in the WGS reaction [11][12][13][14][15]. It is noteworthy that various preparation parameters, such as reaction temperature, reaction time, precursor concentration, solvent, and pH, can be used to modify the characteristics of nanomaterials, including OSC, active metal dispersion, and redox properties.…”
Section: Introductionsupporting
confidence: 65%
“…Consequently, a catalyst with a higher OSC facilitates the acceleration of the redox mechanism governing the WGS reaction [16,36]. Furthermore, previous studies have identified OSC as a key factor in the sulfur resistance of catalysts in the WGS reaction [11,[13][14][15]. Specifically, sulfur adsorbed on the active metal of the Pt/CeO 2 catalyst can react with mobile oxygen derived from the CeO 2 support and subsequently be desorbed in the form of SO 2 [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another two sharp peaks at 71.0 and 74.4 eV are assigned to Pt 4f 7/2 and Pt 4f 5/2 , respectively, further confirming the existence of Pt species. 37,38 The remaining two small satellite peaks are related to the oxidation state of Pt, implying that Pt species grown on the NF existed mainly in the form of metallic Pt, and only a small proportion is in the oxidation state. 39 Notably, as the acid etching concentration increases, the peak area of positivelycharged Pt decreases gradually, which indicates that the acidic conditions can inhibit the adsorption of oxidized Pt on the surface of nickel foam so that the content of positively charged Pt decreases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8,9 In dehydrogenation reactions, due to a concentration gradient of surface hydrogen atoms between generation sites of hydrogen atoms and recombination/desorption sites, "hydrogen reverse spillover" (HRS) is usually observed. 10,11 For example, Rh can recombine hydrogen atoms transferred from metal oxides by reverse spillover to enhance H 2 release over Rh/Fe 3 O 4 -Cr 2 O 3 for the HT-WGSR. 12 In the ammonia borane hydrolysis reaction over NiO/Al 2 O 3 /Pt, using reverse spillover, generated hydrogen atoms on NiO sites are transferred readily to Pt sites for H 2 desorption because the desorption barrier of H 2 is nearly free on Pt.…”
mentioning
confidence: 99%